Evaluation of metabolic, endrocrine and growth features in the Mexican hairless pig to determinate its potential as model for obesity in comparison with commercial pigs - Rogelio A. Alonso Morales; Ma de Lourdes Solano; Fernando Pérez-Gil Romo; Marco A. Herradora Lozano; Rafael Olea Pérez; Carlos G. Gutiérrez; Miguel E. Arechavaleta-Velasco; Carmen Camacho-Rea (Italian Journal of Animal Science, 2010)
Biochemical, endocrine and growth performance variables were evaluated and compared in the Mexican hairless (MHP) and in Landrace Yorkshires pigs (LYP) from first to ninth month of age in order to establish if the MHP could be a better model for the study of obesity than the LYP. Serum concentrations of total cholesterol (TC), triglycerides (TG), high-density lipoproteins (HDL), low-density lipoproteins (LDL), glucose, free fatty acids (FFA), and insulin were measured. Feed intake, body weight and backfat thickness were also monitored. The results showed that the MHP partitioned more energy to backfat than the LYP (P<0.01), and had higher fasting serum concentrations of insulin, TC, TG, LDL, and FFA than the LYP (P<0.05). Based on the high capacity of the MHP to deposit body fat, and its higher serum concentrations of insulin, TG, CT, LDL, and FFA, we conclude that the MHP is a better model for the study of obesity than the Landrace-Yorkshire pigs and could be used under experimental conditions as a model for obesity, particularly the observed in metabolically healthy but obese humans.